Analysis and Design Bank Mini Information System at SMK Negeri 1 Sumenep - Arfilia Septianasari; Sri Hariani Eko Wulandari; Rudi Santoso (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Bank Mini is an accounting lab that used as a student financial payments and saving for students and employees of SMK Negeri 1 Sumenep. Bank Mini managing public savings, special savings, and general payment. Problems exist in Bank Mini is the process of recording transactions and financial reporting using a manual process using the books and records of other transactions, which potentially cause recording and accounting calculations errors. The school wants a Bank Mini information systems, but the schools didn’t know and can’t determine the appropriate system needs to be applied to the Bank Mini. The solution offered is to make the analysis and design of Bank Mini information systems that can generate the analysis and design of recording transaction processes, preparing reports accounting, and reporting of transactions. The process of analysis and design of this research includes the step of collecting data through interview and observation, analysis, system design, and evaluation of system design. The results showed that the analysis and system design can explain design of the transaction recording process, the reporting accounting process, and reporting processes used computing based processing, so it can be used as guidelines for implementation of Bank Mini information systems in the future.